The State of the Acehnese Economy During the Japanese Occupation, 1942-1945: Keadaan Perekonomian Aceh Masa Penjajahan Jepang, 1942-1945 - Umar, Mawardi; Adika Nugraha, Muhammad; Haikal, Muhammad; Kesuma, T. Bahagia (Indonesian Journal of Islamic History and Culture, 2026)
This study examines the economy of Aceh during the Japanese occupation (1942–1945), a critical period in Indonesian history. The Japanese colonial government’s centralized and tightly controlled policies had a significant impact on Aceh’s economic structure, which had previously relied on agriculture, trade, and plantations. The Japanese implemented exploitative economic policies, including the control of natural resources and the seizure of agricultural land, to support the war effort. The consequences included a decline in food production, shortages of basic commodities, and a widespread economic crisis among the population, resulting in a deterioration of the people’s welfare. This study employs a qualitative approach and critical historical research, analyzing primary and secondary sources as well as literature reviews to reconstruct Aceh’s economy under Japanese colonial rule. The findings reveal that the Japanese colonial government dismantled the traditional economic order to support the Greater East Asia Co-Prosperity Sphere’s war machine. The policies of mandatory rice surrender and jatropha cultivation forced the Acehnese people to abandon their traditional subsistence farming practices, leading to mass starvation and chronic food shortages. The circulation of large quantities of Japanese invasion currency triggered hyperinflation that destroyed the people’s purchasing power. The traditional plantation sector also suffered total collapse due to forced land conversion, which severed the export trade chain that had previously been a mainstay of the economy. This Japanese policy has left an economic legacy that has shaped Aceh’s development since independence